Tumor Volume Predicts for Pathologic Complete Response in Rectal Cancer Patients Treated With Neoadjuvant Chemoradiation. (16th September 2022) - Yang, Fan; Hill, Jordan; Abraham, Aswin; Ghosh, Sunita; Steed, Tanner; Kurtz, Clay; Joseph, Kurian; Yun, Jihyun; Warkentin, Brad; Thai, JoAnn; Nijjar, Tirath; Severin, Diane; et al.
Abstract : Objectives: Nonoperative management (NOM) of locally advanced rectal cancer is an emerging approach allowing patients to preserve their anal sphincter. Identifying clinical factors associated with pathologic complete response (pCR) is essential for physicians and patients considering NOM. Materials and Methods: In total, 412 locally advanced rectal cancer patients were included in this retrospective analysis. Tumor volumes were derived from pretreatment MRI. Clinical parameters such as tumor volume, stage, and location were analyzed by univariate and multivariate analysis, against pCR. A receiver operator characteristic curve was generated to identify a tumor volume cut-off with the highest clinically relevant Youden index for predicting pCR. Results: Seventy-five of 412 patients (18%) achieved pCR. A tumor volume threshold of 37.3 cm 3 was identified as predictive for pCR. On regression analysis, a tumor volume >37.3 cm 3 was associated with a greater than 78% probability of not achieving pCR. On multivariate analysis, a GTV <37.3 cm 3 [odds ratio (OR)=3.7, P <0.0001] was significantly associated with an increased pCR rate, whereas tumor length > 4.85 cm was associated with pCR on univariate (OR=3.03, P <0.01) but not on multivariate analysis (OR=1.45, P =0.261). Other clinical parameters did not impact pCR rates. Conclusions: A tumor volume threshold of 37.3 cm 3 was identified as predictive for pCR in locally advanced rectal cancer patients receiving neoadjuvant chemoradiation. Tumors above this volume threshold corresponded to a greater than 78% probability of not achieving pCR. This information will be helpful at diagnosis for clinicians who are considering potential candidates for NOM.